The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jace.14341
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Microwave Dielectric Behavior of A‐Site‐Doped Sr(1−1.5x)CexTiO3 Ceramics System

Abstract: The ion valence state, phase composition, microstructure, and microwave dielectric properties of Sr(1−1.5x)CexTiO3 (x = 0.1–0.67, SCT) ceramics were systematically investigated. Sr(1−1.5x)CexTiO3 ceramics were produced with gradual structural evolution from a cubic to a tetragonal and turned to an orthorhombic structure in the range of 0.1 ≤ x ≤ 0.67. Above a critical Ce proportion (x = 0.4), microstructural changes and normal grain growth initially occurred. On the basis of chemical analysis results, the redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Moreover, the presence of Ce 3+ may inhibit the reduction of Ti 4+ because of the favorable electron compensation. 24 As shown in Fig. 2d, we observed differences in binding energies of Ti-2p core level (Ti-2p3/2 and Ti-2p1/2 spin-orbit splitting) acquired for TiO2 and CeO2-TiO2 hybrid structures.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Moreover, the presence of Ce 3+ may inhibit the reduction of Ti 4+ because of the favorable electron compensation. 24 As shown in Fig. 2d, we observed differences in binding energies of Ti-2p core level (Ti-2p3/2 and Ti-2p1/2 spin-orbit splitting) acquired for TiO2 and CeO2-TiO2 hybrid structures.…”
supporting
confidence: 51%
“…The relative high area ratio O2/O1, (0.38) in the CeO2-TiO2 O-1s spectrum in comparison to that of TiO2 (0.16) could point to an increase of oxygen vacancies. 24 Detailed deconvolution of O-1s core levels is shown in the supplementary information (Fig. S8) The photocatalytic activity of the prepared CeO2-TiO2 hybrid catalyst was first evaluated by degrading Methylene Blue (MB) under ultra-violet (UV) light irradiation (in comparison to bare TiO2) as shown in Fig.…”
mentioning
confidence: 99%
“…As some ions tend to segregate at the grain boundaries, the growth of grain is restrained. 19 As a result, the grains tend to become small and uniform with the increment of doping content. As presented in Figure 2 (C) and (D), the average grain size decreases to~1.30 lm when x = 0.1 and becomes a little smaller at x = 0.15.…”
Section: Resultsmentioning
confidence: 99%
“…(1-x)Mg(Ti 0.95 Sn 0.05 )O 3 -xBaTiO 3 compounds experienced a phase transition of tetragonal-structure BaTiO 3 , monoclinic-structure Ba 4 Ti 11 O 26 , and triclinic-structure Ba 2 Ti 9 O 20 [419]. Likewise, Sr (1-1.5x) Ce x TiO 3 (x = 0.1-0.67) ceramics changed from cubic, tetragonal, to orthorhombic, and the dielectric behaviors were dominated by oxygen vacancies and defect dipoles [420]. Tian et al [421,422] reported that (Co 0.5 W 0.5 ) 4+ and (Zn 0.5 W 0.5 ) 4+ occupying the Ti-site in BaTiO 3 would render the τ f value change from positive to negative.…”
Section: Abo 3 Formulamentioning
confidence: 99%